Numerical Solutions for Fed-Batch Fermentation Process by Using Leapfrog Method - Sasikala, P.; Vijayarakavan, M. (International Journal of Engineering and Technology, 2018)
This article is in detail the dynamical models of two non-linear systems of fed-batch and group aging procedures about consequences of the investigation. With a specific end goal to comprehend the state conditions for the non-linear system and Leapfrog Method for the combination of the non-linear differential equations were produced. The stated algorithm has extended to incorporate with the different non-linearity problems.Â